Tetradentate Palladium(II) Salophen Complexes: Synthesis, Characterization and Catalytic Activities in Copper-Free Sonogashira Coupling Reaction - Nizam Ahmad, Shahrul; Bahron, Hadariah; Mohd Tajuddin, Amalina (International Journal of Engineering and Technology, 2018)
This paper reports the synthesis and characterization of three salophen ligands; 2,2'-((1E,1'E)-(1,2 phenylenebis(azanylylidene))bis(methanylylidene))diphenol [L1H], 2,2'-((1E,1'E)-(1,2-phenylenebis(azanylylidene))bis (methanylylidene))bis(4-chlorophenol) [L1C] and 2,2'-((1E,1'E)-(1,2-phenylenebis(azanylylidene))bis(methanylylidene))bis(4-methoxylphenol) [L1OME]. The compounds were prepared from condensation reaction between salicylaldehyde, and its derivatives, with ortho-phenylenediamine. Their palladium(II) complexes, namely PdL1H, PdL1C and PdL1OME were synthesized through insertion reaction between the ligands with palladium(II) acetate. All compounds were characterized through melting point, elemental analysis, infrared spectroscopy, 1H and 13C NMR spectroscopy. Palladium(II) complexes were tested as homogenous catalysts in copper-free Sonogashira coupling reaction between iodobenzene and phenylacetylene in DMSO using triethylamine as base with 1.0 mmol% catalyst loading. The most performing catalyst was PdL1OME with 91% conversion followed by PdL1H (83%) and PdL1C (27%).Â Â Â